THE DEVELOPMENT OF ENGLISH LINGUISTICS: A HISTORICAL OVERVIEW (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article explores the evolution of English linguistics from its origins in Old English to the contemporary study of the language. It highlights key historical periods, including the influence of the Norman Conquest on Middle English, the standardization processes during the Early Modern English era, and the scientific advancements of the 19th century. The rise of structuralism in the 20th century is discussed alongside contemporary trends such as sociolinguistics and the impact of technology on language. By tracing these developments, the article illustrates how English linguistics has adapted to social, cultural, and technological changes, reflecting the language's dynamic nature and its role in global communication.